Perinatal Exposure of Bisphenol A Differently Affects Dendritic Spines of Male and Female Grown-Up Adult Hippocampal Neurons - Kawato, Suguru; Ogiue-Ikeda, Mari; Soma, Mika; Yoshino, Hinako; Kominami, Toshihiro; Saito, Minoru; Aou, Shuji; Hojo, Yasushi (Frontiers in Neuroscience, 2021)
Perinatal exposure to Bisphenol A (BPA) at a very low dose may modulate the development of synapses of the hippocampus during growth to adulthood. Here, we demonstrate that perinatal exposure to 30 μg BPA/kg per mother’s body weight/day significantly altered the dendritic spines of the grownup rat hippocampus. The density of the spine was analyzed by imaging of Lucifer Yellow-injected CA1 glutamatergic neurons in adult hippocampal slices. In offspring 3-month male hippocampus, the total spine density was significantly decreased by BPA exposure from 2.26 spines/μm (control, no BPA exposure) to 1.96 spines/μm (BPA exposure). BPA exposure considerably changed the normal 4-day estrous cycle of offspring 3-month females, resulting in a 4∼5 day estrous cycle with 2-day estrus stages in most of the subjects. In the offspring 3-month female hippocampus, the total spine density was significantly increased by BPA exposure at estrus stage from 2.04 spines/μm (control) to 2.25 spines/μm (BPA exposure). On the other hand, the total spine density at the proestrus stage was moderately decreased from 2.33 spines/μm (control) to 2.19 spines/μm (BPA exposure). Thus, after the perinatal exposure to BPA, the total spine density in males became lower than that in females. Concerning the BPA effect on the morphology of spines, the large-head spine was significantly changed with its significant decrease in males and moderate change in females.